Phenomenon of differentiation as a basic condition for inclusion in primary education - Monika Semradova (International Journal of Studies in Inclusive Education)
This study focuses on the current trend of increasing the quality of education, which brings with it increased demands on teacher competences in the implementation of differentiated instruction for primary students from the very beginning of schooling. The key subject of the study investigation is the inclusive concept of differentiated instruction, which represents a complex modification of the educational content, process, product and evaluation of the educational process. According to the Strategies of Educational Policy of the Czech Republic until 2030+, ensuring comparable and high-quality teaching in primary schools by introducing internal differentiation and individualisation is a key strategy for improving heterogeneous collectives' teaching quality. However, teachers are not sufficiently prepared for this reality, and very little relevant literature exists. Using a qualitative study design that includes participant observation and semi-structured interviews with seven teachers from three regions of the Czech Republic, this paper seeks to systematically map the implementation of these pedagogical strategies in the years 2021-2023 with first- and second-year primary students in the subjects of Czech language and mathematics. A multi-case study of seven teachers presents a longitudinal study of the implementation of differentiated teaching strategies with a focus on its inclusive concept, which is reflected in all components of the educational process. This dissertation highlights the urgent need for further study in this critically important area, especially considering the lack of exploration of pedagogical means of differentiation and individualisation in the Czech study field.